A Robust Integrated SnOx/Carbon Composite Anode for Sodium‐Ion Batteries. Issue 39 (22nd October 2018) - Xu, Jia; Shen, Lu; Shi, Kai; Cao, Tengfei; Lv, Wei; He, Yan‐Bing
Abstract: Tin (Sn) has been considered as a promising anode material for sodium ion battery due to its high specific capacity. However, its poor cycling stability and rate performance hinders the real application. Inspired by the structure of reinforced concrete and tunnel, an integrated SnOx /carbon composite anode was designed for high performance sodium ion batteries. In this structure, the SnOx nanoparticles were embedded in the amorphous carbon with interconnected pores derived from carbonization of the polyacrylonitrile (PAN) and starch, where the amorphous carbon can buffer the bulk expansion of SnOx to maintain structural stability and the interconnected pores can store the electrolyte to promote the sodium ion transportation for high rate reaction of the SnOx particles with sodium ion. The reduced graphene oxide as robust framework similar with rebar is inserted into the amorphous carbon/SnOx composite to enhance the stability and conductivity of composite. The starch as pore‐creating additive is decomposed during high‐heat treatment to form interconnected tunnel‐like pores in SnOx /carbon composite for electrolyte storage and high efficient sodium ion transportation. As a result, the as‐prepared integrated SnOx /carbon composite anode shows outstanding rate and cycling performance. Constructing the interconnected pore in SnOx /carbon composite using starch can greatly improve its charge specific capacity and rate performance. Abstract : A robust integrated SnOx /carbon composite anode with high rate and cycling performance is designed and prepared in the light of rebar concrete structure. The SnOx nanoparticles are embedded in the amorphous carbon with interconnected pores that can store the electrolyte to promote the sodium ion transportation for high rate reaction of the SnOx nanoparticles with sodium ion. The reduced graphene oxide is inserted into integrated SnOx /carbon to enhance its stability and conductivity.